2017
DOI: 10.1007/s10815-017-1069-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in products of conception of first-trimester miscarriages detected by conventional cytogenetic analysis: a review of 1000 cases

Abstract: Approximately, 50% of first-trimester miscarriages have chromosomal abnormalities which can be detected by conventional cytogenetic analysis. The presence of chromosomal abnormality may explain the cause of miscarriage, improving the reproductive counseling and planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 39 publications
4
61
0
Order By: Relevance
“…Importantly, CCRs are hardly ever detected during conventional karyotyping of chorion cells in a miscarriage, which is conducted starting from 4 to 5 weeks of gestation (i.e., after embryo implantation) (Pendina et al, 2014; Massalska et al, 2017; Soler et al, 2017; Pylyp et al, 2018). As of today, the literature describes only one case of CC in an embryo with multiple malformations (Macera et al, 2015).…”
Section: Constitutional Chromothripsis As a Consequence Of Genome Dammentioning
confidence: 99%
“…Importantly, CCRs are hardly ever detected during conventional karyotyping of chorion cells in a miscarriage, which is conducted starting from 4 to 5 weeks of gestation (i.e., after embryo implantation) (Pendina et al, 2014; Massalska et al, 2017; Soler et al, 2017; Pylyp et al, 2018). As of today, the literature describes only one case of CC in an embryo with multiple malformations (Macera et al, 2015).…”
Section: Constitutional Chromothripsis As a Consequence Of Genome Dammentioning
confidence: 99%
“…Recently, it has been demonstrated that fetal DNA can be isolated from maternal circulation, although this technique is reliable only for identification of trisomies 21, 18, and 13 (13). In addition, copy number variation sequencing (CNV-seq) analysis can be implemented to detect clinically significant fetal abnormalities but problems remain in interpretation of CNV (14) Until now, few studies have focused on the incidence of chromosomal abnormalities in prenatal samples among pregnant women in southern China. The main purpose of the present study was to evaluate the frequency and type of fetal chromosomal abnormalities among pregnant women following an abnormal ultrasound, positive serological screen, or noninvasive prenatal testing (NIPT) result or those with AMA or a history of miscarriage, to provide valuable information for prenatal counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Providers who care for women with early pregnancy loss have the option to send products of conception for chromosome analysis. If abnormal, these genetic results can provide an explanation for a pregnancy loss, which has been shown to correlate with lower rates of anxiety and self-blame following a pregnancy loss (8) However, data show that a euploid miscarriage is a risk factor for subsequent euploid miscarriage, suggesting maternal rather than chromosomal factors are the cause for spontaneous miscarriage and further evaluation should be performed (9).…”
mentioning
confidence: 99%